the solution of the given system of equations is x=-43/14 and y=-92/21.
Given the system of equations as below: \(\[ \begin{cases}2x-3y=7\\4x+5y=8\end{cases}\]\)
The main answer is the solution for the system of equations. We can solve the system of equations by using the elimination method.
\(\[\begin{aligned}2x-3y&=7\\4x+5y&=8\\\end{aligned}\\)
]Multiplying the first equation by 5, we get,\(\[\begin{aligned}5\cdot (2x-3y)&=5\cdot 7\\10x-15y&=35\\4x+5y&=8\end{aligned}\]\)
Adding both equations, we get,\(\[10x-15y+4x+5y=35+8\][\Rightarrow 14x=-43\]\)
Dividing by 14, we get,\(\[x=-\frac{43}{14}\]\) Putting this value of x in the first equation of the system,\(\[\begin{aligned}2x-3y&=7\\2\left(-\frac{43}{14}\right)-3y&=7\\-\frac{86}{14}-3y&=7\\\Rightarrow -86-42y&=7\cdot 14\\\Rightarrow -86-42y&=98\\\Rightarrow -42y&=98+86=184\\\Rightarrow y&=-\frac{92}{21}\end{aligned}\]\)
in the given system of equations, we have to find the values of x and y. To find these, we used the elimination method. In this method, we multiply one of the equations with a suitable constant to make the coefficient of one variable equal in both the equations and then we add both the equations to eliminate one variable.
Here, we multiplied the first equation by 5 to make the coefficient of y equal in both the equations. After adding both the equations, we got the value of x. We substituted this value of x in one of the given equations and then we got the value of y. Hence, we got the solution for the system of equations.
To know more about equations visit:
brainly.com/question/29657983
#SPJ11
find all values of x for which the perimeter is at most 32
Answer:
0 < x ≤ 11
Step-by-step explanation:
perimeter = (x - 6) + (x - 6) + x + x
⇒ perimeter = 4x - 12
If the perimeter is "at most 32" then
4x - 12 ≤ 32
⇒ 4x ≤ 44
⇒ x ≤ 11
Therefore, 0 < x ≤ 11
11. Which statement suggests causation?
a) When you are at the beach, you get
wet.
b) When you study for a test, your
classmate studies too.
c) When you carry an umbrella to school,
it rains.
d) When you don't brush your teeth, you
get cavities.
Two families go to a zoo.
The Smith family of two adults and three children pay £61.
The Jones family of three adults and five children pay £96.
Work out the cost of an adult ticket and the cost of a child ticket.
Answer:
The adult tickets cost £17.00 and child tickets cost £9.00
Step-by-step explanation:
2a + 3c = 61
2a = 61 - 3c
a = 30.5 - 1.5c
3(30.5 - 1.5c) + 5c = 96
91.5 - 4.5c + 5c = 96
91.5 + 0.5c = 96
0.5c = 4.5
c = 9
a = 30.5 - 1.5c
a = 17
The adult tickets cost £17.00 and child tickets cost £9.00
What is the quotient of 3/5 divided by 9/20
find the average value of the function over the given interval. f(z) = 3z2 − 2z on [−3, 4]
Thus, the average value of the function f(z) = 3z² − 2z on the interval [−3, 4] is 128/42.
To find the average value of the function f(z) = 3z² − 2z on the interval [−3, 4], we need to use the formula for the average value of a function over an interval. The formula is given as:
Average value = 1/(b-a) * ∫f(z) dz from a to b
where a and b are the lower and upper limits of the interval.
In our case, a = -3 and b = 4, so we have:
Average value = 1/(4-(-3)) * ∫3z² − 2z dz from -3 to 4
Simplifying the integral, we get:
Average value = 1/7 * [(3z³/3) - (2z²/2)] from -3 to 4
Average value = 1/7 * [(64/3) - (18/2) - (-27/3) + (6/2)]
Average value = 1/7 * [(64/3) - 9/2 + 9/3]
Average value = 1/7 * [(64/3) - 9/2 + 27/6]
Average value = 1/7 * [(128/6) - 27/6 + 27/6]
Average value = 1/7 * 128/6
Average value = 128/42
Therefore, the average value of the function f(z) = 3z² − 2z on the interval [−3, 4] is 128/42. This means that if we were to take all the values of the function on this interval and find their average, it would be equal to 128/42.
Know more about the average value
https://brainly.com/question/30460573
#SPJ11
Mark
the absolute maximum point of the graph.
Answer:
6
Step-by-step explanation:
Answer:
Point (0,6)
Step-by-step explanation:
Point (0,6) is the highest point plotted on the graph.
suppose the number of calls received at a call center follows a poisson distribution. suppose the average time between calls received at a call center is 2 minutes. what is the probability that the waiting time until the next call is more than three minutes
So the probability that the waiting time until the next call is more than three minutes is approximately 0.223.
The Poisson distribution is a probability distribution that describes the number of events occurring in a fixed interval of time or space, given that these events occur independently and at a constant rate.
In this case, we are dealing with the number of calls received at a call center, and we are told that the average time between calls is 2 minutes.
If the number of calls follows a Poisson distribution, we can use the Poisson probability formula to calculate the probability of getting a certain number of calls in a given time period.
However, in this case, we are interested in the waiting time until the next call, which is not directly related to the number of calls. To solve this problem, we can use the fact that the time between two consecutive calls follows an exponential distribution,
which is a continuous probability distribution that describes the time between two events occurring independently and at a constant rate.
The probability density function of the exponential distribution is given by f(x) = λe^(-λx), where λ is the rate parameter (i.e., the reciprocal of the average time between events) and x is the waiting time.
In this case, λ = 1/2 (since the average time between calls is 2 minutes), and we are interested in the probability that the waiting time until the next call is more than three minutes. This can be expressed mathematically as P(X > 3), where X is the waiting time.
To calculate this probability, we can use the cumulative distribution function (CDF) of the exponential distribution, which gives the probability that X is less than or equal to a certain value.
The CDF of the exponential distribution is given by F(x) = 1 - e^(-λx). Therefore, P(X > 3) = 1 - P(X ≤ 3) = 1 - F(3) = 1 - (1 - e^(-1.5)) = e^(-1.5) ≈ 0.223, So the probability that the waiting time until the next call is more than three minutes is approximately 0.223.
This means that there is about a 22.3% chance that the call center will not receive a call for more than three minutes, given that the calls arrive independently and at a constant rate.
To know more about probability click here
brainly.com/question/15124899
#SPJ11
The depth of water at a dock can be modeled as y = 4 sin (62) + 9. At lowtide, the water is 5 feet deep. What is the depth of water at high tide (itsmaximum point)?A. 18 feetB. 14 feetC. 9 feetD. 13 feet
Step 1:
Re-state the given function.
\(y=4\sin (\frac{\pi}{6}x)+9\)Step 2:
We shall state the mathematical implication of the sine function at both minimum and maximum points.
At minimum point:
\(\begin{gathered} At\text{ minimum point: }\sin (\frac{\pi}{6}x)=-1 \\ \text{Similarly,} \\ At\text{ maxi}mum\text{ point: }\sin (\frac{\pi}{6}x)=1 \end{gathered}\)Step 3: We shall substitute the values in step 2 above in the given function.
We are only interested in the value at maximum point, so
\(\begin{gathered} y=4(1)+9 \\ y=4+9 \\ y=13\text{ fe}et \end{gathered}\)Thus, the correct answer is 13 feet ( option D)
The preference relation ≽ satisfies monotonicity if for all x, y ∈ X, if xk ≥ yk for all k, then x ≽ y, and if xk > yk for all k, then x ≻ y.
The preference relation ≽ satisfies strong monotonicity if for all x, y ∈ X, if xk ≥ yk for all k and x ≠ y then x ≻ y.
Show that preferences represented by min{x1, x2} satisfy monotonicity but not strong monotonicity
If we contrast the different parts, x1 = 3 2 = y1 and x2 = 4 4 = y2 are the results.
To show that preferences represented by min{x₁, x₂} satisfy monotonicity but not strong monotonicity, we need to demonstrate two things:
Preferences satisfy monotonicity: If xᵢ ≥ yᵢ for all i, then x ≽ y, and if xᵢ > yᵢ for all i, then x ≻ y.
Preferences do not satisfy strong monotonicity: There exist x and y such that xᵢ ≥ yᵢ for all i, but x ≠ y, and x ≰ y.
Let's address each of these points:
Monotonicity:
Suppose x and y are two bundles such that xᵢ ≥ yᵢ for all i. We need to show that x ≽ y and x ≻ y.
First, note that min{x₁, x₂} represents the minimum value between x₁ and x₂, and the same applies to y₁ and y₂.
Since x₁ ≥ y₁ and x₂ ≥ y₂, we can conclude that min{x₁, x₂} ≥ min{y₁, y₂}.
Therefore, x ≽ y, indicating that if all components of x are greater than or equal to the corresponding components of y, then x is weakly preferred to y.
However, if x₁ > y₁ and x₂ > y₂, then min{x₁, x₂} > min{y₁, y₂}. Hence, x ≻ y, indicating that if all components of x are strictly greater than the corresponding components of y, then x is strictly preferred to y.
Thus, preferences represented by min{x₁, x₂} satisfy monotonicity.
Strong Monotonicity:
To show that preferences represented by min{x₁, x₂} do not satisfy strong monotonicity, we need to provide an example of x and y such that xᵢ ≥ yᵢ for all i, but x ≠ y, and x ≰ y.
Consider the following bundles:
x = (3, 4)
y = (2, 4)
In this case, x₁ > y₁ and x₂ = y₂, so x ≻ y.
However,Thus, xᵢ ≥ yᵢ for all i, but x ≠ y, and x ≰ y.If we compare the individual components, x₁ = 3 ≥ 2 = y₁ and x₂ = 4 ≥ 4 = y₂.
Therefore, preferences represented by min{x₁, x₂} satisfy monotonicity but not strong monotonicity.
learn more about contrast from given link
https://brainly.com/question/2477099
#SPJ11
f(x) = 3x + 5
g(x) = 4x² - 2
h(x) = x²-3x+1
Find f(x) + g(x) - h(x).
O 3x² + 6x + 2
-O 3x²+2
O 6x2² +6x-1
O 5x² +4
After solving the expression we get 3x² ₊ 6x ₊ 2 .
Given f(x) = 3x₊5
g(x) = 4x² ₋ 2
h(x) = x² ₋ 3x ₊ 1
f(x) ₊ g(x) ₋ h(x)
substitute the values.
3x ₊ 5 ₊ 4x² ₋ 2 ₋ (x² ₋ 3x ₊ 1)
4x² ₊ 3x ₊ 3 ₋ x² ₊ 3x ₋ 1
3x² ₊ 6x ₊ 2
hence we get 3x² ₊ 6x ₊ 2 .
Learn more about Functions here:
brainly.com/question/15602982
#SPJ9
Evaluate the derivative of the function f(t)=7t+4/5t−1 at the point (3,25/14 )
The derivative of the function f(t) = (7t + 4)/(5t − 1) at the point (3, 25/14) is -3/14.At the point (3, 25/14), the function f(t) = (7t + 4)/(5t − 1) has a derivative of -3/14, indicating a negative slope.
To evaluate the derivative of the function f(t) = (7t + 4) / (5t - 1) at the point (3, 25/14), we'll first find the derivative of f(t) and then substitute t = 3 into the derivative.
To find the derivative, we can use the quotient rule. Let's denote f'(t) as the derivative of f(t):
f(t) = (7t + 4) / (5t - 1)
f'(t) = [(5t - 1)(7) - (7t + 4)(5)] / (5t - 1)^2
Simplifying the numerator:
f'(t) = (35t - 7 - 35t - 20) / (5t - 1)^2
f'(t) = (-27) / (5t - 1)^2
Now, substitute t = 3 into the derivative:
f'(3) = (-27) / (5(3) - 1)^2
= (-27) / (15 - 1)^2
= (-27) / (14)^2
= (-27) / 196
So, the derivative of f(t) at the point (3, 25/14) is -27/196.The derivative represents the slope of the tangent line to the curve of the function at a specific point.
In this case, the slope of the function f(t) = (7t + 4) / (5t - 1) at t = 3 is -27/196, indicating a negative slope. This suggests that the function is decreasing at that point.
To learn more about derivative, click here:
brainly.com/question/25324584
#SPJ11
a binomial experiment with probability of success and trials is conducted. what is the probability that the experiment results in or fewer successes?
In a binomial experiment with probability of success and trials is conducted, the probability of one trial is independent of another.
How to find the number of success in a binomial distribution?
The likelihood of success is constant from trial to trial, and subsequent trials are independent. A binomial expression, which derives from counting successes across a series of trials, has just two possible outcomes on each trial.
One of the two outcomes, known as success or failure, arises from every try. From trial to trial, the chance of success, indicated by the symbol p, stays constant. There are n independent trials. In other words, the probability of one trial do not influence those of the others.
Therefore, in a binomial experiment with probability of success and trials is conducted, the probability of onetrial is independent of another.
To learn more about binomial distribution refer to:
brainly.com/question/9325204
#SPJ4
(4x – 5)(7 – 2x) – (2x + 2)(2 – 4x)= -1
Answer: x= 19/21.
Step-by-step explanation:
We can expand the expression to:
28x - 8x^2 - 35 + 10x -4x + 8x^2 - 4 + 8x = -1
We can then cancel the - 8x^2 and the + 8x^2 and simplify further by adding like terms:
38x - 35 + 4x -4 = -1 --> 42x - 39 = -1
We can then add 39 on both sides:
42x = 38
We can then divide both sides by the GCF (greatest common factor), 2:
21x = 19
We divide both sides by 21:
x = 19/21
Kyan earned 80% of what he made last week. If he made $72 this week, how much did he make last week?
Answer:
$90
Step-by-step explanation:
7200/80=90
Answer:
$111
Step-by-step explanation: 80 divided by 72 is 111.
A student made the table to find 40% of 130. 20% 20% 20% 20% 20% = 100% 0.2 0.2 0.2 0.2 0.2 = 1 26 26 26 26 26 = 130
Which expression can be used find 40% of 130?
(26) (5)
(26) (4)
(26) (3)
(26) (2)
Answer:
(26) (5) ( A ) Would be you answer. Have a Great day.
Step-by-step explanation:
Answer:
Your answer is A.
Step-by-step explanation:
I got it right!
Which equation below has infinite solutions?
A) 2x + 5 = 2x + 8
B) 5x – 1= 2x + 4
C) x + 9 = x + 9
D) 4x 1 = 6x + 2
Answer:
C) x + 9 = x + 9
Step-by-step explanation:
An equation has infinite solutions if can simplify to the format: a = a, where a is any number.
This is because it means that any value you plug into x will give you the same true equation and answer.
C meets these requirements as it is already in format a=a, but if we further simplify it, we can see how it works:
Subtract x from both sides: 9=9
Subtract 9 from both sides: x=x
Subtract (x+9) from both sides: 0=0
We can see that C has infinite solutions because any value you put in for x, it will cancel itself out when you solve it, therefore it has infinite solutions.
E.g. x=5
(5) + 9 = (5) + 9
14 = 14
E.g. x=-25
(-25) + 9 = (-25) = 9
-16 = -16
We can also answer this question by solving all the other equations:
A) 2x + 5 - 2x = 2x - 2x + 8
5 = 8
This is not true so this equation has NO solutions.
B) 5x - 2x - 1 = 2x - 2x + 4
3x - 1 + 1 = 4 + 1
3x = 5
x = 5/3 (One solution)
D) I think you've missed a sign here, but it is solvable either way to get to one solution.
Hope this helped!
Which of the following polynomial equations has 1, 4, -5 as three of its roots?
x 2+4x-5=0
x 4+2x 3-5x+10=0
x 3-21x+20=0*
Answer: x³-21x+20=0
Step-by-step explanation:
To find which polynomial has 1, 4, -5 as the roots, all we have to do is equal each root to 0 and multiply all factors together.
1 is (x-1)=0
4 is (x-4)=0
-5 is (x+5)=0
Now, we just multiply them together.
(x-1)(x-4)(x+5)=0 [FOIL]
(x²-4x-x+4)(x+5)=0 [combine like terms]
(x²-5x+4)(x+5)=0 [FOIL]
x³+5x²-5x²-25x+4x+20=0 [combine like terms]
x³-21x+20=0
Now we know x³-21x+20=0 is the polynomial with those roots.
What is the quotient for the expression 2,314 divided by 4
Answer:
578.5
Step-by-step explanation:
The area of a rectangle is represented by the
polynomial 6r^2+ 3x - 30. Which expressions
could represent the sides of the rectangle?
F 2y — 5 and 3r + 6
G 2y + 5 and 3r - 6
H 2r + 5 and 3r + 6
I 21 - 5 and 3x
Answer:
2 is the right answer
I say your answer
Unit 7 polygons and quadrilaterals
Homework 7 trapezoids
** this is a 2-page document **
Directions: if each quadrilateral below is a trapezoid, find the missing measures
Angle L can be calculated as follows:
angle L = angle - 180 LMO stands for angle. MNO \sangle L = 180 - 150 - 30 degree angle L = 0
As a result, angle L is 0 degrees.
1. We know that sides AB and CD of trapezoid ABCD are parallel. We can use the tangent function to find the length of side AD because angle B is a right angle and angle ABD is 45 degrees:
AD/AB = tan(45)
AD=AB * tan(45) AD=AB
As a result, AD = 10.
2. We know that the sides PQ and RS of the trapezoid PQRS are parallel. We can use the sine function to find the length of side PS because angle Q is a right angle and angle PSQ is 60 degrees:
PS/QS sin(60) =
PS = sin * QS (60)
5 * sqrt = PS (3)
As a result, PS = 5*sqrt (3).
3. We know that the sides UV and WX of a trapezoid UVWX are parallel. We can use the cosine function to find the length of side WU because angle V is a right angle and angle WVU is 30 degrees:
WU/UV cos(30) =
UV * cos WU (30)
5 * sqrt(3) / 2 = WU
As a result, WU = (5/2)*sqrt (3).
4. We know that the sides LM and NO of the trapezoid LMNO are parallel. We can use the sine function to find the length of side MO because angle L is a right angle and angle MNO is 30 degrees:
MO/NO sin(30) =
MO = 4 / 2 MO = NO * sin(30)
As a result, MO = 2.
Because angles MNO and LMO add up to 180 degrees, we can calculate angle LMO as follows:
LMO angle = 180 - angle LMO MNO angle = 150 degrees
Finally, because angle N is a right angle, we can calculate angle L as follows:
angle L = angle - 180 LMO stands for angle. MNO\sangle L = 180 - 150 - 30 degree angle L = 0
As a result, angle L is 0 degrees.
To know more about Length visit:
https://brainly.com/question/30100801
#SPJ1
1
A power line is connecting the top of a building to the ground 251.8 meters away from the base of the building. At what angle is the wire connected at the
building (angle of depression) if the wire is 371.9 meters long?
four students write algebraic math expressions and equations on their whiteboard. Which of the following students wrote expressions?
Answer:
Expressions: Student 1 and 4
Equations: Student 2 and 3
Step-by-step explanation:
Equations have an = sign. Expressions do not.
Given: F(x)= 5 x - 6 and G(x)= x - 4
(FoG)^-1=
By definition of inverse function,
\(F\left(F^{-1}(x)\right) = x\)
so that
\(5F^{-1}(x) - 6 = x\)
\(5F^{-1}(x) = x + 6\)
\(F^{-1}(x) = \dfrac{x + 6}5\)
Similarly,
\(G\left(G^{-1}(x)\right) = G^{-1}(x) - 4 = x \implies G^{-1}(x) = x+4\)
Then the inverse of the composition \(F\circ G\) is such that
\(\left(F \circ G\right) \left((F \circ G)^{-1}(x)\right) = x\)
By definition of composition,
\((F\circ G)(x) = F(G(x))\)
Applying \((F\circ G)^{-1}\) to this recovers x, and this involves first inverting F, then G:
\((F\circ G)^{-1}(x) = G^{-1}\left(F^{-1}(x)\right)\)
So, we find
\((F\circ G)^{-1}(x) = G^{-1}\left(F^{-1}(x)\right) = G^{-1}\left(\dfrac{x+6}5\right) = \dfrac{x+6}5 + 4 = \boxed{\dfrac{x+26}5}\)
A wave travels 5/4, mile in 1/12 hour. At this rate, how far will the wave travel in 1 hour? Find the unit rate.
can someone plz help me with this question asap: solve the equation for x in the terms of c. 2/3(cx + 1/2) - 1/4 = 5/2
A: x = 9/4c
B: x = 27/8c
C: x = 29/8c
D: x = 29/18c
In the diagram shown at the right, ABCD is a parallelogram and BF = 16. Find the area of ABCD. Explain your reasoning. (Hint: Draw auxiliary lines through point A and through point D that are parallel to EH.)
The above question is a mathematical proof of the relationship between Lines and angles related to a Rhombus. See the proof below.
We know,
A Rhombus is a parallelogram with four sides (that is a quadrilateral). It's sides however are all of equal length.
we have,
∠DEC ≅ ∠BFC Reason = All Right Angles with Equal dimensions are congruent.
∠C ≅ ∠C Reason = It is the same angle for the two Right angles above which are congruent, hence Reflexive Property.
Δ DEC ≅ Δ BFC Reason = Angle Angle Side. The triangles are said to be congruent when two angles and a non-included side of one triangle match the corresponding angles and sides of another triangle.
≅ Reason = The corresponding parts of congruent triangles are congruent. Also, it is a parallelogram with all congruent sides.
ABCD is a Rhombus Reason = Its sides are all congruent.
Learn more about Rhombus at;
brainly.com/question/20627264
#SPJ1
complete question:
Given: ABCD is a parallelogram, FC is congruent to EC, DE bisects BC and BF bisects DC Prove: ABCD is a rhombus
Question 10(Multiple Choice Worth 5 points)
(Identifying Functions LC)
The graph represents a relation where x represents the independent variable and y represents the dependent variable.
a graph with points plotted at negative 5 comma 1, at negative 2 comma 0, at negative 1 comma 3, at negative 1 comma negative 2, at 0 comma 2, and at 5 comma 1
Is the relation a function? Explain.
No, because for each input there is not exactly one output.
No, because for each output there is not exactly one input.
Yes, because for each input there is exactly one output.
Yes, because for each output there is exactly one input.
Is the relation a function:
No, because for each input there is not exactly one output.How to know if the relation is a functionTo determine if the relation is a function, we need to check if there is exactly one output for each input.
Looking at the given set of points, we see that there are two points with an x-coordinate of -1: (-1, 3) and (-1, -2).
This means that there are two outputs for the same input, so the relation is not a function.
Therefore, the correct answer is: "No, because for each input there is not exactly one output."
Learn more about graphs at
https://brainly.com/question/19040584
#SPJ1
what is the circomfrence of the circle r = 4 ft
Answer:
C≈25.13ft
Step-by-step explanation:
C=2πr=2·π·4≈25.13274ft
Find the limit of the following sequence or determine that the limit does not exist. ((-2)} Select the correct choice below and, if necessary, fill in the answer box to complete your choice. OA. The sequence is not monotonic. The sequence is not bounded. The sequence converges, and the limit is-(Type an exact answer (Type an exact answer.) OB. The sequence is monotonic. The sequence is bounded. The sequence converges, and the limit is OC. The sequence is not monotonic. The sequence is bounded. The sequence converges, and the limit is OD. The sequence is not monotonic. The sequence is not bounded. The sequence diverges.
The correct choice is the sequence is not monotonic. The sequence is bounded. The sequence converges, and the limit is -2 (option c).
The given sequence (-2) does not vary with the index n, as it is a constant sequence. Therefore, the sequence is both monotonic and bounded.
Since the sequence is bounded and monotonic (in this case, it is non-decreasing), we can conclude that the sequence converges.
The limit of a constant sequence is equal to the constant value itself. In this case, the limit of the sequence (-2) is -2.
Therefore, the correct choice is:
OC. The sequence is not monotonic. The sequence is bounded. The sequence converges, and the limit is -2.
To know more about sequence:
https://brainly.com/question/30262438
#SPJ4
The limit of the sequence is -2.
Given sequence is ((-2)}
To find the limit of the given sequence, we have to use the following formula:
Lim n→∞ anwhere a_n is the nth term of the sequence.
So, here a_n = -2 for all n.
Now,Lim n→∞ a_n= Lim n→∞ (-2)= -2
Therefore, the limit of the given sequence is -2.
Also, the sequence is not monotonic. But the sequence is bounded.
So, the correct choice is:
The sequence is not monotonic.
The sequence is bounded.
The sequence converges, and the limit is -2.
learn more about sequence on:
https://brainly.com/question/28036578
#SPJ11
Malik’s solution to the equation , when , is shown below.
Question: What is the Question?